A Geographical Study of Smart Infrastructures in Jaipur Smart City : जयपुर स्मार्ट सिटी में स्मार्ट आधारभूत संरचनाओं का एक भौगोलिक अध्ययन - Ashutosh; Chaudhary, Anita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In a new phase of urbanization, Jaipur Smart City aspires to enhance the quality of life for its citizens by leveraging innovative and inclusive resources, while also capitalizing on its rich cultural and historical heritage and tourism potential. Jaipur is India’s tenth-largest metropolitan area and has emerged as a prominent hub for tourism, trade, commerce, and education. Due to its historical legacy and status as the capital of Rajasthan, Jaipur has long been a focal point of visionary strategies by successive state governments. Consequently, efforts are being made to develop it as a ‘world-class’ city. Following its inclusion in the Government of India’s Smart City Program, significant expectations have emerged regarding improvements in urban infrastructure. Under the Smart City Mission, the objective is to promote economic growth and enhance citizens’ quality of life through comprehensive interventions across the city’s social, economic, physical, and institutional pillars. The mission aims to provide a clean and sustainable environment and to carry forward development activities in such a manner that Jaipur becomes a beacon city for other aspirational cities in the Smart City Mission. This paper outlines the framework of Jaipur’s urban infrastructure and addresses emerging urban infrastructural challenges with a focus on management and governance. Abstract in Hindi Language: नगरीकरण के एक नए चरण में जयपुर स्मार्ट सिटी अपने नागरिकों के जीवन की गुणवत्ता को बढ़ाने हेतु अभिनव और समावेशी संसाधनों के माध्यम से अपनी सांस्कृतिक एवं ऐतिहासिक विरासत और पर्यटन का लाभ उठाने की इच्छा रखती है। जयपुर भारत का दसवां सबसे बड़ा महानगरीय क्षेत्र है, जो एक लोकप्रिय पर्यटन स्थल, व्यापार, वाणिज्य और शिक्षा का केंद्र बिंदु बनकर उभरा है। ऐतिहासिक विरासत और राजस्थान की राजधानी होने के कारण यह राज्य सरकारों की दूरदर्शी रणनीतियों का केंद्र बिंदु रहा है, इसलिए इसे ‘विश्व स्तरीय’ शहर के रूप में विकसित करने के प्रयास किए जा रहे हैं। इसी चरण में भारत सरकार द्वारा स्मार्ट सिटी कार्यक्रम में जयपुर शहर को शामिल किए जाने के बाद, शहर में बड़े पैमाने पर शहरी संरचना में सुधार की उम्मीदें जगी हैं। स्मार्ट सिटी मिशन के तहत शहर के सामाजिक, आर्थिक, भौतिक और संस्थागत स्तंभों पर व्यापक कार्यों के माध्यम से आर्थिक विकास को बढ़ावा देना और नागरिकों के जीवन की गुणवत्ता स्तर में सुधार करना है। इसका उद्देश्य स्वच्छ और टिकाऊ वातावरण प्रदान करना और विकास गतिविधियों को इस तरह से आगे बढ़ाना है कि शहर स्मार्ट सिटी मिशन में अन्य महत्वाकांक्षी शहरों के लिए एक प्रकाश स्तंभ के रूप में कार्य करे। यह लेख जयपुर शहर की आधारभूत संरचना की रूपरेखा प्रस्तुत करता है, इसके बाद प्रबंधन और शासन पर ध्यान केंद्रित करते हुए उभरती शहरी अवसंरचनात्मक चुनौतियों की खोज का समाधान करता है। Keywords: स्मार्ट सिटी, अवसंरचनात्मक, नियोजन, स्वच्छ और टिकाऊ विकास, गोल्डन ट्राईंगल, एरिया बेस डवलपमेंट, ई-शासन, इंटरनेट ऑफ थिंग्स